En studie av en klinisk population inom späd- och småbarnspsykiatrin-relationen mellan föräldrars anknytningsmönster, föräldrastress och kontaktanledning. - Kathy,Nora; Radomski Workneh,Hanna (2018)
In child and infant mental health clinics families are treated for a variety of reasons. It may be that the feelings expressed for the child by the parent may not be as expected, due to the mental health problems of the parent, or that the relationship between the child and parent is filled with conflict, or that there is a parental concern for the child's symptoms. This study aimed at investigating and describing the clinical population in two child and infant mental health clinics in Skåne. The study had the design of a descriptive, cross-sectional study in which all parents who started treatment were asked to participate. The study was based on 73 parents who filled in self-assessment forms. Distinctions between parents with different attachment patterns were investigated in relation to parental stress and reason for contact. Gender differences were also explored. The results showed that the parents in this study had a significantly higher incidence of symptoms of mental health issues, higher parental stress and insecure attachment compared to the normal population. The parents with ambivalent attachment patterns had significantly higher parental stress than the other parents. The parents who sought contact for child-related problems had a significantly higher parental stress than those who sought for parent-related problems. The mothers showed significantly higher parental stress than the fathers. The majority of parents lived in pair relationships and had a high level of education. Clinical implications are that the importance of both early detection of high parental stress as well as the parents’ attachment patterns and reasons for contact, should be considered when regarding appropriate treatment.
Keywords: Anknytningsmönster; Föräldrastress; Kontaktanledning; Parental Stress Index (PSI); Relationship Questionnaire (RQ); attachment patterns; parental stress; reason for contact